National and International Policies Governing Haze in Malaysia: a Move Forward towards a Greener Future - Syahirah Abdul Shukor; Hanim Kamaruddin; Dina Imam Supaat; Rasyikah Mohd Khalid; Normawati Hashim (Science Publishing Corporation Inc, 2024)
Indexed by Scopus/ERA